Plataforma youtube como principal fuente de ingreso para jóvenes en Ecuador - Benavides Mejia, Jordan Maiky (2021)
The digital platform & quot;YouTube" was born as a communication strategy in order to create content, this led to the birth of "Youtubers", people who are dedicated to developing, uploading and sharing information applying strategies to obtain economic profitability. The objective of this project was to analyze the YouTube social network as the main source of income for young people in Ecuador. It was also sought to identify and explain the factors that influence this environment. To carry out this research, the qualitative methodology was used, which makes it possible to collect necessary informational resources from the internet and the digital medium, in order to observe the videos posted on the network of the channel of these characters. In the investigation we were able to know that the usefulness of youtubers always depends on the amount of advertising spaces that they manage to publish among their videos. The profit of content creators depends on advertising and in turn, on the territory and local currency; the profit obtained is shared with google, and in our country there is still no “Partner” or monetization system existing in other countries.